Large German Multicenter Experience on the Treatment Outcome of 207 Patients With Adenoid Cystic Carcinoma of the Major Salivary Glands - Akbaba, Sati; Bostel, Tilman; Lang, Kristin; Bahadir, Suzan; Lipman, Djoeri; Schmidberger, Heinz; Matthias, Christoph; Rotter, Nicole; Knopf, Andreas; Freudlsperger, Christian; Plinkert, Peter; Debus, Juergen; et al. (Frontiers in Oncology, 2020)
Introduction: We aimed to evaluate treatment outcome of combined radiotherapy (RT) including photon intensity modulated radiotherapy (IMRT) and carbon ion boost for adenoid cystic carcinomas (ACCs) of the major salivary glands, the currently available largest German collective for this cohort. Materials and Methods: Overall, 207 patients who were irradiated with combined RT between 2009 and 2019 at Heidelberg University Hospital were analyzed retrospectively for local control (LC), progression-free survival (PFS) and overall survival (OS) using Kaplan-Meier estimates. 85% of the patients received postoperative RT (n=176/207) after previous surgery in large German hospitals mainly Mainz, Freiburg, Mannheim and Heidelberg University Hospitals and 15% received primary RT (n=31/207). Results: After a median follow-up time of 50 months, 84% of the patients were still alive (n=174/207). Disease progression occurred in 32% of the patients (n=66/207) while local recurrence was diagnosed in 12% (n=25/207), and distant relapse in 27% (n=56/207). Estimated 5-year LC, PFS and OS rates were 84%, 56% and 83% for OS, respectively. In multivariate analysis, we could identify two prognostic subgroups: one subgroup resulting in decreased LC, PFS and OS rates and another subgroup having an additional survival disadvantage in PFS and OS. Patients with a macroscopic tumor disease (yes vs. no; p<0.001 for LC, p=0.010 for PFS and p=0.040 for OS) treated in a definitive setting (vs. postoperative setting; p=0.001 for LC, p=0.006 for PFS, p=0.049 for OS) and tumors of upper T stage (T1-4; p=0.004 for LC, p<0.001 for PFS, p<0.001 for OS) showed significantly more local relapses and a decreased PFS and OS. Upper Age (p<0.001 for both PFS and OS), lower Karnofsky Performance Score (<80% vs. ≥80%; p<0.001 for both PFS and OS) and solid histology (vs. non-solid; p=0.049 for PFS and p=0.003 for OS) were in addition associated with worse survival outcome. Toxicity was moderate with 18% late grade 2 and 3 toxicity. Conclusions: Combined RT results in superior LC rates compared to photon data with moderate toxicity. In multivariate analysis, upper T stage, the existence of a macroscopic tumor before RT and definitive RT setting were identified as major prognostic factors affecting LC negatively.